Relationship Marketing and Supply Chain policy in Enhancing the Customer Value in the Telecommunication Sector - Hafsa Atallah Hussein; Bilal .J Al-Qaysi (International Journal of Supply Chain Management, 2019)
The purpose of this study was to investigate the effect of alignment of marketing strategies on the supply chain and organizational performance in the Telecommunication Sector. The purpose of this research is practical, and in terms of nature and method, it is a descriptive-survey research of correlation type. The communication creations became one of the huge projects in Iraq during the last few years, yet at the year 2005 these projects was manipulated by one or two firms, yet , there are now more than five firms working in this field, we can notice that the Iraqi customer has no loyalty toward any specific company or firm because of their reputation, moreover he/she is ready to abandon any firm in order to obtain low price services, which led to intense the marketing efforts by other firms win and keep the current customers in the Iraqi market. This situation forced the firms to reform working strategies to improve the competition advantage, From the above discussion, it will be clear that the research proposal for this study is to identify and verify the relationship between marketing and quality in the process of creating and delivering value to customers. And this was made through the use of the questionnaire, followed by analysis of the collected data and a conceptual framework based on the results. The researchers used questionnaires, and the total sample reached 1257 among the involved customers in the communication company in Iraq, and more specific in Baghdad the involved ages where between (18-40) years, %43 females, and %57 males. The authors have used 5 point Likert scale. The proposed hypothesis of the study: relationship marketing (perceived service quality, trust, customer satisfaction, the Corporate Image) has a positive effect on customer value.The result was a (perceived service quality, trust, customer satisfaction) has a positive effect on customer value, while the Corporate Image. Does not has a positive effect on customer value.